The involvement of extension agent in planning, implementing and monitoring paddy cultivation project based on rice check at IADA Seberang Perak - Azizan, Nurnabilah (2016)
Rice is the main food in Malaysia and it is categorized the important crop after oil palm. Malaysia only achieved 73% of self-sufficiency and that is not enough to feed Malaysian. Paddy productivity in Malaysia can be classified low. There are large gap between potential yields with current yield in Malaysia. Government has support various research especially agency such as Malaysia Agricultural Research and Development Institute (MARDI) to do research and produce new variety to improve paddy yield in Malaysia. DOA had produced Manual Paddy Technology and Rice Check technology since 2002. A new variety which is MR219 has been produced by MARDI. The potential yield of the variety is 10mtan/ha however after 13 years been release the yield do not achieve as potential yield. According to DOA (2013) the variety had been grown by the majority of farmers from eight (8) granaries in Malaysia. The problem is why the yield do not achieved target? We want to study whether extension agent involvement is related to the problem or not. This study was carried out with the purpose to identify work performance and involvement of extension agent in deliver rice check technology in Seberang Perak. Respondent consists of 150 farmers from 4 blocks; block A, C, D and F. The result of involvement level in objective setting is high, planning is high, implementing is high, monitoring is high and work performance is also high. Monitoring activities show high correlation with work performance. Regression analysis from this survey shows that monitoring and objective setting are highly significant with performance. Objective setting and monitoring activities are strongly related to work performance. For recommendation, extension agents are advice to improve in objective setting and monitoring as it is significant with work performance In conclusion, monitoring and objective setting are important aspects for extension agents in transferring technology.